RESEARCH AND ANALYSIS OF THE TECHNOLOGY OF RESTORATION OF HYDRO-TECHNICAL STRUCTURES OF TRANSPORTATION BUILDING FROM CULVERTS BY THE SLEATHING METHOD - Artur Onyshchenko; Inna Harkusha; Mykola Harkusha; Mykola Klymenko (Дороги і мости, 2023)
Introduction. Hydrotechnical structures of transport construction from road culverts are used to pass water under roadways and other structures. One of the ways to increase the durability and reliability of road culverts is to carry out repairs by the sleeve method. The proposed method involves the installation of a new road culvert in the middle of a defective road culvert, and the space between the pipes is filled with mortar. The distribution of the mixture will further determine the effectiveness of the applied restoration method and the reliability of the repaired structure. The relevance of the work consists in determining the efficiency of filling the inter-pipe space with mortar.